Local government capacity building and development: lessons, challenges and opportunities - Chakunda, Vincent (2020)
The conceptualisation of capacity building is rather an oversimplified subject but is a very complex and in most cases one which has been misappropriated by scholars and practitioners. The term capability, capacity and capacity building have become the rhetoric of public officials and students of Local governances who have unfortunately misconceptualised them. The notion of local government and community capacity building is both explicit and pervasive in the rhetoric, missions, and activities of a broad range of contemporary community development efforts. However, there is limited clarity about the meaning of capacity and capacity building and development which clarification becomes one of the central discourses of this paper. Against this background an extensive conceptual analysis of capacity development, reflecting its historicity, elasticity and dynamic nature will anchor this paper. Justification for local government capacity building and a contextual analysis of local capacity development in Zimbabwe, particularly the Rural District Councils Capacity Building Programme (RDCCBP) and the Urban 1 and 2 programmes will be reviewed on a case by case basis.